1984
DOI: 10.1111/j.1751-1097.1984.tb04641.x
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of the Excited States of 2‐phenylbenzoxazole by Azide Anion. Fluorescence and Esr Study

Abstract: Electron spin resonance, spin‐trapping and fluorescence techniques demonstrate that 2‐phenylbenzoxazole (P) participates in photo‐induced reactions with alcohols and electron donors like the azide ion. Irradiation of Pat 300 nm in deaerated ethanol produces ethoxyl and hydroxyethyl radicals which can be detected with the spin trap, 5,5‐dimethyl‐l‐pyrroline‐l‐oxide (DMPO). However, irradiation of P in the presence of N‐3 leads to the appearance of the azide radical, N‐3, which also reacts with DMPO. Studies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The oxidizing properties of both PBSA and PBI are clearly shown by their reactions with azide. Sodium azide reacts with photoexcited PBSA to form the azidyl radical and quenches PBSA fluorescence with a rate constant of 4.46 ϫ 10 9 M Ϫ1 s Ϫ1 , consistent with values reported earlier (18). This rate constant for PBSA reflects a strong interaction between the singlet excited state of PBSA and the azide anion and strongly suggests that the excited singlet state of PBSA is oxidizing in nature.…”
Section: Photooxidizing Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…The oxidizing properties of both PBSA and PBI are clearly shown by their reactions with azide. Sodium azide reacts with photoexcited PBSA to form the azidyl radical and quenches PBSA fluorescence with a rate constant of 4.46 ϫ 10 9 M Ϫ1 s Ϫ1 , consistent with values reported earlier (18). This rate constant for PBSA reflects a strong interaction between the singlet excited state of PBSA and the azide anion and strongly suggests that the excited singlet state of PBSA is oxidizing in nature.…”
Section: Photooxidizing Propertiessupporting
confidence: 88%
“…We examined the potential of the excited singlet state of PBSA to accept electrons by measuring its fluorescence in the presence of sodium azide. Sodium azide has been shown to quench the fluorescence of a compound structurally similar to PBI, namely, 2-phenylben-zoxazole (2-PBO) (18). It was suggested that this quenching could be caused by electron transfer from the azide anion to the singlet state of 2-PBO.…”
Section: Photochemistrymentioning
confidence: 99%
“…A similar, photoinduced decay of nitroxide radicals in the presence of photosensitizers has been reported previously. [32] We also observed the decay of TEMPOL in a separate set of experiments, where we worked with intentionally oxygen-depleted aqueous solutions of various fullerene-based photosensitizers (data not shown). Therefore, the marked change in the ESR signal intensity of TEM-POL observed after 25 min of illumination ( Fig.…”
Section: Full Papermentioning
confidence: 93%
“…The sulfur analogues of alkoxyl radicals (thiyls) are also trapped at fast rate constants (-lo8 M-I s-' ) (13). spin trapping studies have suggested that oxygen-centered radicals may be important intermediates in radiolysis (14) and sonolysis (15) reactions, ozone-related chemistry (16,17), xanthinelxanthine oxidase systems (18), carcinogenesis (19), antitumour drug redox interactions (20)(21)(22), cigarette smoke (23), druglskin phototoxicity (24,25), neutrophil action (26a-c), peroxidation reactions (27)(28)(29)(30)(31), as well as myocardial ischemia/reperfusion injury (32a-c).…”
mentioning
confidence: 99%